2021
DOI: 10.1049/gtd2.12216
|View full text |Cite
|
Sign up to set email alerts
|

Research on the assessment of the capacity of urban distribution networks to accept electric vehicles based on the improved TOPSIS method

Abstract: This study proposes a TOPSIS-based method for assessing the ability of distribution networks to accept electric vehicles. This method establishes an assessment index system in terms of the rationality, safety, and economy of the distribution network operation, and assesses the capacity of the distribution network in all aspects. Firstly, a fuzzy theory-based model of users' charging psychology under the influence of time-of-use electricity price was constructed, and the spatio-temporal distribution of EV charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…To quantitatively evaluate the impact of Saihanba restoration on the environment, we established the evaluation model of Saihanba's impact on the ecological environment by using the TOPSIS comprehensive evaluation method. TOPSIS comprehensive evaluation method [7,8] , also known as the ranking method of approaching an ideal solution, belongs to the common method in multi-objective decision analysis. First, establish the positive and negative ideal solutions, corresponding to the maximum and minimum values of the standardized evaluation index.…”
Section: Topsis Comprehensive Evaluation Methods On the Ecological En...mentioning
confidence: 99%
“…To quantitatively evaluate the impact of Saihanba restoration on the environment, we established the evaluation model of Saihanba's impact on the ecological environment by using the TOPSIS comprehensive evaluation method. TOPSIS comprehensive evaluation method [7,8] , also known as the ranking method of approaching an ideal solution, belongs to the common method in multi-objective decision analysis. First, establish the positive and negative ideal solutions, corresponding to the maximum and minimum values of the standardized evaluation index.…”
Section: Topsis Comprehensive Evaluation Methods On the Ecological En...mentioning
confidence: 99%
“…It has a small amount of calculation, less information distortion, and intuitive geometric significance. The accuracy of the calculation is not affected by the number of indicators (Zhang et al, 2021). The basic idea of TOPSIS is to calculate the Euclidean distance (Ekmekciog˘lu et al, 2021) between each evaluation scheme and the positive and negative ideal solutions and to calculate the relative closeness coefficient between each evaluation scheme and the ideal solution.…”
Section: Topsis Modelmentioning
confidence: 99%
“…The number of vehicles in the residential distribution network, the penetration of plug-in hybrid electric vehicles (PHEVs) in the next few years, the distribution of PHEVs in the network, and the estimated household load growth in the next few years have been considered to study the impact of EVs on the residential distribution system; however, other distribution systems such as industrial areas have not been considered [18]. The evaluation index system has been established from the three aspects of rationality, safety, and economy of the distribution network operation, and the capacity of the distribution network has been evaluated from various aspects [19]. The analysis of EV access from the two aspects of distribution network construction investment and network loss during operation has shown that EV access will lead to an increase in both the distribution network investment cost and the network loss [20].…”
Section: Introductionmentioning
confidence: 99%